An Impedance-Based Approach for Sensing Cyclodextrin-Mediated Modulation of Membrane Cholesterol - Bint E Naser, Samavi Farnush (Langmuir : the ACS journal of surfaces and colloids, 2023)
Cyclodextrin molecules are increasingly being used in biological research and as therapeutic agents to alter membrane cholesterol content, yet there is much to learn about their interactions with cell membranes. We present a biomembrane-based organic electronic platform capable of detecting interactions of cell membrane constituents with methyl-β-cyclodextrin (MβCD). This approach enables label-free sensing and quantification of changes in membrane integrity resulting from such interactions. In this work, we employ cholesterol-containing supported lipid bilayers (SLBs) formed on conducting polymer-coated electrodes to investigate how MβCD impacts membrane resistance. By examining the outcomes of MβCD interactions with SLBs of varying cholesterol content, we demonstrate that changes in membrane permeability or resistance can be used as a functional measure for predicting cyclodextrin-mediated cholesterol extraction from cellular membranes. Furthermore, we use the SLB platforms to electronically monitor cholesterol delivery to membranes following exposure to MβCD pre-loaded with cholesterol, observing that cholesterol enrichment is commensurate with an increase in resistance. This biomembrane-based bioelectronic sensing system offers a tool to quantify the modulation of membrane cholesterol content using membrane resistance and provides information regarding MβCD-mediated changes in membrane integrity. Given the importance of membrane integrity for barrier function in cells, such knowledge is essential for our fundamental understanding of MβCD as a membrane cholesterol modulator and therapeutic delivery vehicle